Assessing adherence to hypertension medications and its impact on blood pressure control: A community-based observational study - Sandhya Rani M,; Ramesh Palabindela,; Penupothu Sree Nagamani,; Naveen Choudary G, (Asian Journal of Medical Sciences, 2023)
Background: Hypertension is a prevalent cardiovascular condition requiring effective medication management for blood pressure control. Aims and Objectives: The aim is to explore the relationship between adherence to hypertension medications and its impact on blood pressure control among a diverse population. Materials and Methods: A participant cohort of 500 adults, with a mean age of 56 years, was examined for their adherence to hypertension medications and blood pressure control outcomes. Adherence was assessed through self-report questionnaires and pill count analysis, while blood pressure control was defined as systolic blood pressure below 140 mmHg and diastolic blood pressure below 90 mmHg. The statistical analysis included logistic regression with adjustments for potential confounding variables. Results: The participant cohort displayed a balanced gender distribution and predominantly managed hypertension through multi-drug regimens. Around 65% reported high medication adherence, confirmed by pill count analysis. Notably, 55% achieved the defined blood pressure control target, indicating effective management. A robust association was observed between high adherence and improved blood pressure control (adjusted odds ratio=1.65, 95% confidence interval: 1.28–2.12, P<0.001). Participants with high adherence were 1.65 times more likely to attain target blood pressure control than those with lower adherence, with a high level of statistical significance. Conclusions: This study highlights the crucial link between medication adherence and blood pressure control in hypertensive individuals. High adherence increases the likelihood of optimal blood pressure control, underscoring patient commitment. Tailored interventions and support mechanisms are essential for enhancing adherence and improving hypertension management outcomes.